Case Report: Surgery combined with targeted therapy for metastatic anorectal malignant mucosal melanoma - Yao, Yadong; Liu, Pule; Liu, Kai; Lian, Lirong; Gao, Shuo (Frontiers in Oncology, 2025)
BackgroundAnorectal mucosal melanoma is a rare tumor with a poor prognosis. Timely diagnosis and treatment are essential for improving patient survival. Currently, there is no standardized treatment approach for this disease. This case report emphasizes the effectiveness of combining surgery with targeted therapy for advanced KIT-mutated anorectal mucosal melanoma, as well as the potential adverse effects during targeted therapy.Case reportWe report a 66-year-old female diagnosed with primary anorectal mucosal melanoma with liver metastasis. She underwent a transanal local excision to remove the primary anorectal mucosal melanoma and ultrasound-guided radiofrequency ablation for the liver metastasis. After surgery, she received targeted therapy with imatinib due to the presence of c-Kit mutations. The results showed the expected clinical efficacy. Unfortunately, the patient later developed portal vein thrombosis and liver dysfunction during the imatinib therapy, necessitating the discontinuation of targeted therapy.ConclusionsThe combination of transanal local excision of the primary lesion and radiofrequency ablation of liver metastases, complemented by imatinib-targeted therapy, represents a feasible therapeutic strategy for advanced KIT-mutated anorectal mucosal melanoma. This strategy may prolong patient survival; however, potential adverse events require careful monitoring.